The benefits, risks and costs of privacy: patient preferences and willingness to pay. (4th May 2017) - Trachtenbarg, David E.; Asche, Carl; Ramsahai, Shweta; Duling, Joy; Ren, Jinma
Abstract: Objective: Multiple surveys show that patients want medical privacy; however, there are costs to maintaining privacy. There are also risks if information is not shared. A review of previous surveys found that most surveys asked questions about patient's privacy concerns and willingness to share their medical information. We found only one study that asked about sharing medical information for better care and no survey that asked patients about the risk, cost or comparison between medical privacy and privacy in other areas. To fill this gap, we designed a survey to: (1) compare medical privacy preferences to privacy preferences in other areas; (2) measure willingness to pay the cost of additional privacy measures; and (3) measure willingness to accept the risks of not sharing information. Methods: A total of 834 patients attending physician offices at 14 sites completed all or part of an anonymous questionnaire. Results: Over 95% of patients were willing to share all their medical information with their treating physicians. There was no difference in willingness to share between primary care and specialty sites including psychiatry and an HIV clinic. In our survey, there was no difference in sharing preference between standard medical information and information with additional legal protections including genetic testing, drug/alcohol treatment and HIV results. Medical privacy was ranked lower than sharing social security and credit card numbers, but was deemed more private than other information including tax returns and handgun purchases. There was no statistical difference for any questions by site except for HIV/AIDS clinic patients ranking privacy of the medical record more important than reducing high medical costs and risk of medical errors ( p < .05). Most patients were willing to spend a modest amount of additional time for privacy, but few were willing to pay more for additional medical privacy. Most patients were unwilling to take on additional risks to keep medical information hidden. Conclusions: Patients were very willing to share medical information with their providers. They were able to see the importance of sharing medical information to provide the best possible care. They were unwilling to hide information from providers if there was increased medical risk. Patients were willing to spend additional time for privacy, but most were unwilling to spend extra money. Sixty-eight percent of patients favored reducing medical costs over privacy.